Perhitungan Tonase Stockpile Batubara Metode Cut and Fill Menggunakan Aplikasi Minescape - Itsnani SM, A. Arifin; Riansyah, Riansyah; Sutaji, Ahmad Aris Mundir (Journal of Geomatics Engineering, Technology, and Science, 2024)
Coal is a mineral resource with high economic value. Demand for coal commodities is increasing to meet energy needs. Therefore, calculating coal reserves is an important thing to do in coal exploration activities. Coal that has been mined will be stacked in a storage area (stockpile) or temporary storage (temporary stock) before being transported to consumers. Periodic volume monitoring is one of the most important things in stockpile management control which aims to determine the volume of coal in the stockpile. The cut and fill method is a coal volume calculation method that is often used in mining activities by calculating the area of ​​two cross-sections and the distance between the top and bottom cross-sections. The data used in this research are coordinate data (x, y, and z) stock taking measurements, base/bedding data (base), weighing data, density data (density), and ortho photos of Port SBJ obtained indirectly from the location research at PT Insani Baraperkasa, Tani Bhakti Village, Loa Janan District, Kutai Kartanegara Regency. The results of this research are the total BCM (Bank Cubic Meter) volume of the coal stockpile, which is then converted into tonnage value (kg/m³), namely by multiplying the density (kg/m³) of coal to obtain the tonnage value in Raw Coal Room 1, namely 33,012.52 (tons) and the Crushed Coal tonnage is 8,080.07 (tons). The tonnage value adds up to 41,092.59 (tons) in the SBJ Port stockpile tonnage for the period February 2022.